Dickeya Manipulates Multiple Quorum Sensing Systems to Control Virulence and Collective Behaviors - Liu, Fan; Hu, Ming; Zhang, Zhijia; Xue, Yang; Chen, Shanshan; Hu, Anqun; Zhang, Lian-hui; Zhou, Jianuan (Frontiers in Plant Science, 2022)
Soft rot Pectobacteriaceae (SRP), typical of Pectobacterium and Dickeya, are a class of Gram-negative bacterial pathogens that cause devastating diseases on a wide range of crops and ornamental plants worldwide. Quorum sensing (QS) is a cell-cell communication mechanism regulating the expression of specific genes by releasing QS signal molecules associated with cell density, in most cases, involving in the vital process of virulence and infection. In recent years, several types of QS systems have been uncovered in Dickeya pathogens to control diverse biological behaviors, especially bacterial pathogenicity and transkingdom interactions. This review depicts an integral QS regulation network of Dickeya, elaborates in detail the regulation of specific QS system on different biological functions of the pathogens and hosts, aiming at providing a systematic overview of Dickeya pathogenicity and interactions with hosts, and, finally, expects the future prospective of effectively controlling the bacterial soft rot disease caused by Dickeya by quenching the key QS signal.